2016
DOI: 10.3109/09638288.2015.1111434
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia in Duchenne muscular dystrophy: practical recommendations to guide management

Abstract: Purpose: Duchenne muscular dystrophy (DMD) is a rapidly progressive neuromuscular disorder causing weakness of the skeletal, respiratory, cardiac and oropharyngeal muscles with up to one third of young men reporting difficulty swallowing (dysphagia). Recent studies on dysphagia in DMD clarify the pathophysiology of swallowing disorders and offer new tools for its assessment but little guidance is available for its management. This paper aims to provide a step-by-step algorithm to facilitate clinical decisions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(94 citation statements)
references
References 46 publications
0
70
0
2
Order By: Relevance
“…Anticipatory assessment for dysphagia is important and should be done regularly. 118 Screening questions should focus on perceived difficulty with swallowing of liquids and solids, perception of food sticking in the throat, time necessary to eat an average meal, and interference of eating with quality of life. 119 If a patient responds to screening questions in the affirmative, the speech-language pathologist should be consulted for a comprehensive assessment, including a video fluoroscopic swallowing study.…”
Section: Gastrointestinal and Nutritional Managementmentioning
confidence: 99%
“…Anticipatory assessment for dysphagia is important and should be done regularly. 118 Screening questions should focus on perceived difficulty with swallowing of liquids and solids, perception of food sticking in the throat, time necessary to eat an average meal, and interference of eating with quality of life. 119 If a patient responds to screening questions in the affirmative, the speech-language pathologist should be consulted for a comprehensive assessment, including a video fluoroscopic swallowing study.…”
Section: Gastrointestinal and Nutritional Managementmentioning
confidence: 99%
“…First, all assessments that involve large volumes of liquids may put the patient at risk of aspiration and choking. Second, they only provide a snapshot in time and do not consider factors such as fatigability or ventilation . Fatigue is an important factor in patients with muscle weakness.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired swallow, also called dysphagia, is a frequent symptom in NMD that occurs in 34.9% to 80% of patients, depending on the disease age group and the severity . Prevalence in paediatric patients with neuromuscular diseases (pNMD) seems to be similar to adult patients .…”
mentioning
confidence: 99%
“…The current study indicated that 70.6% of children with NMDs had chewing disorder at different levels. There are studies which reported the presence of chewing problems in children with NMDs and its possible reasons . However, there is no study to show the specific nature of the chewing disorders in these children in the literature.…”
Section: Discussionmentioning
confidence: 99%